Highly stable barium zirconate supported nickel oxide catalyst for dry reforming of methane: From powders toward shaped catalysts - Seo, Minhye; Kim, Soong Yeon; Kim, Young Dok; Park, Eun Duck; Uhm, Sunghyun (International Journal of Hydrogen Energy, 2018)
We report the barium zirconate supported NiOx catalysts (NiOx/BZO) for dry reforming of methane and feasibility test for their industrial application by using temperature-regulated chemical vapor deposition together with extrusion. Nickel oxide nanoparticles are well deposited and dispersed on BZO powders as well as structures in a gear form, showing high catalytic activity and extraordinary stability even at relatively lower temperature and higher space velocity. The NiOx/BZO catalyst are highly coke resistant for 50 h operation with almost negligible agglomeration of NiOx nanoparticles. Judging from XPS and high ion conducting properties of BZO supports, the –OH or –O species are expected to play an important role in promoting the self-decoking of surface carbon species to form CO and CO2.
Keywords: Decoking; Dry reforming-of-methane; Feasibility tests; Ion conducting properties; Lower temperatures; Nickel oxide nanoparticle; Space velocities; Supported nickel; Barium zirconate; Dry reforming of methane; Self-decoking; Shaped catalysts; Temperature-regulated chemical vapor deposition